(untitled) (Research, Society and Development, 2022)
Introduction: The role of the community health agent in Primary Care is fundamental, as it is the link between the community and the health team. In the development of work activities, these professionals face many challenges, which can generate frustration and hopelessness, causing psychological distress. Objective: To understand the factors that generate mental suffering in the work routine of community health agents. Method: Qualitative research, using semi-structured interviews carried out between August and September 2020 with seven community health agents working in a Basic Health Unit in Iguatu- Ceará. The empirical material generated was transcribed and analyzed using thematic Content Analysis technique. Results: The work context generates psychological distress because it is permeated by pressure, demands, many impasses in the micro-area, accumulation of work and the challenge of being a resident, worker and user of health services in the same territory. Conclusion: It is necessary to plan actions to improve the work process of the community health agent, in order to reduce mental suffering and improve the quality of life of these workers.